Pengaruh Brand Image, Harga dan Kualitas Produk Terhadap Brand Loyalty Kecap Bango - Nurrahman, Iqbal; Utami, Hesty Nurul; Suminartika, Eti; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The decline in Kecap Bango's Top Brand Index over recent years highlights the need for evaluating the factors influencing brand loyalty. This study aims to analyze the impact of brand image, price, and product quality on the brand loyalty of Kecap Bango. Data were collected through a survey of 80 respondents who are consumers of Kecap Bango at Toko X, Cirebon, and analyzed using multiple linear regression methods. The results indicate that brand image and price significantly influence brand loyalty, while product quality does not have a significant effect. Simultaneously, brand image, price, and product quality collectively have a positive impact on brand loyalty. These findings emphasize the importance of strengthening brand image and setting competitive pricing in building brand loyalty, ultimately supporting the enhancement of Kecap Bango's brand performance.